Fiscal policy: a study on the relationship between government expenditure with gross domestic product, national income and unemployment in Malaysia / Nik Nor Azizi Nik Mohd Salleh - Mohd Salleh, Nik Nor Azizi Nik (2006)
The purpose of this research is to observe the relationship between economic indicators with government expenditure. The economic indicators are Gross Domestic Product, private consumption, and unemployment. The data from the year 1996 to 2005 by using quarterly basis were collected to determine whether the variables have significant relationship or not. Through the previous research, there are different results obtained. Some of the researchers found that there is no significant relationship between government expenditure and GDP, and the others found there is a significant relationship between government expenditure and GDP. Based on the literature review, majority of the researchers found there is a significant relationship between government expenditure and private consumption. Private consumption is expected to decline after a positive government spending shock. It is very hard to proof the relationship between government expenditure with unemployment. However, the result from regression analysis shows that both variables have significant relationship.